Maquiavelos «Senza Virtù»: About the Realities of Political Realism - José Antonio García Saez (Comillas Journal of International Relations, 2019)
Hans J. Morgenthau is one of the most representative authors of realism in international relations. His work, however, has been received in Spain and other countries in a biased way, fundamentally by neglecting those moral elements of his theory. This work deals with some of the elements of the classic realism of the 20th century. Also, it shows some particularities of Morgenthau’s realism, pointing out some of its main contemporary developments and influences.